Pteronemobius yuani Ma & Wang sp. nov. and Metiochodes tianfuensis Ma, Yuan & Gu sp. nov., new species of Trigonidiidae from China (Orthoptera: Trigonidiidae; Trigonidiinae) - Wang, Rui; Yuan, Wei; Zheng, Yan-Na; Gu, Jun-Jie; Ma, Li-Bin (Zootaxa, 2023)
The article describes two new species of Trigonidiidae Saussure, 1874, namely Pteronemobius yuani Ma & Wang sp. nov. and Metiochodes tianfuensis Ma, Yuan & Gu sp. nov. The former belongs to Pteronemobius Jacobson, 1904, and is similar to Pteronemobius gifuensis (Shiraki, 1911) but has a long and narrow epiphallic median lobe, and the outer posterior tibia is armed with three dorsal spurs; while the latter belongs to Metiochodes Chopard, 1932, which is similar to Metiochodes flavescens Chopard, 1932, but the epiphallic median lobe is concave. Here, we describe and illustrate these new species.